AN ANALYSIS OF INTERACTIONAL PATTERN BETWEEN TEACHER AND STUDENT IN SMAN 1 CURUP KOTA - Hendi Afriyanto; Alamsyah Harahap; Azwandi Azwandi (JOALL (Journal of Applied Linguistics and Literature), 2018)
This study investigates the interaction pattern in SMAN 1 Curup Kota, based on Coulthard theory (2002). This study analyzed the interaction pattern and type of act used by teacher and students to see the ideal pattern in the classroom. The data analysis shows that (a) the dominant pattern used in the classroom is complete pattern (IRF) and there are also semi-complete pattern (IR) and incomplete pattern (IF); (b) In the type of acts section, the elicitation is the highest followed by informative and starter in the initiation move,  reply as the highest act in the response move, and in the follow up accept as the highest followed by comment. It can be concluded that interaction pattern in the classroom is dominantly occured is ideal pattern but it’s not good interaction pattern because delimit student opportunity in the classroom.